Effect of Positive Role Model on Young Girls - Altendorfer, Katherine M. (My University, 2016)
This project focuses on the effect that an older role model or mentor can have on a younger girl regarding her attitude toward health and self-image. It looks at attitudes toward exercise, eating habits, self-esteem, and various other health topics. The data was collected through Wildcat Wellness Coaching, and the subjects were young females generally between the ages of 8 and 12. Some of the girls were exposed to Wildcat Wellness Coaching that taught them how to prepare healthy snacks and make exercising more fun. The other girls were exposed to Wildcat Wellness Coaching that taught them about important health topics that may affect them in the future. This program allowed them to meet with a coach weekly for about an hour. Each semester the participants were different and their progress was monitored from start to finish. Results showed a change in attitude of the girls who participated in one of the interventions, but not in the other.